The Coping mechanism by school children in response to the psychosocial impact of flood disaster: case study at Ernakulam, Kerala India - Mubarak, Niseetha Parveen; Noremy Md. Akhir,; Mohd Suhaimi Mohamad,; Nur Saadah Mohamad Aun, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Flood disasters profoundly impact school children in Kerala, particularly in Ernakulam, disrupting their lives, education, and emotional well-being. Despite the critical need for support, there is limited understanding of how these children cope with the psychosocial challenges posed by floods. This study aims to explore these coping mechanisms to inform effective mental health support and resilience-building programs in schools. Using a qualitative design with a case study approach, eight school children were purposively sampled. Data collection revealed four primary themes: regulating anxiety, the role of a multidisciplinary approach, the development of resilient behaviour, and rebuilding physical health. Regulating anxiety involves emotional regulation strategies, psychosocial support, and continuous mental health assessment, with family, peers, and professionals playing critical roles in providing support. A multidisciplinary approach, including integrated parental support, child-cantered methodologies, and capacity-building initiatives, is essential for effective adaptation, with educators, healthcare providers, and community leaders fostering a supportive environment. Resilient behaviour is exhibited through adaptability, a rebuilding spirit, and altruistic tendencies despite challenges, highlighting the need for targeted interventions for children showing post-traumatic behaviours. Rebuilding physical health addresses psychosomatic issues, general health challenges, and malnutrition, emphasizing the necessity of integrating physical health concerns with psychosocial interventions. Overall, the findings stress the importance of comprehensive, child-focused interventions that combine emotional, social, and physical health support to enhance the well-being of flood-affected children in Ernakulam.